Deep ASKAP EMU Survey of the GAMA23 field: properties of radio sources. Issue 4 (11th April 2022) - Gürkan, Gülay; Prandoni, I; O'Brien, A; Raja, W; Marchetti, L; Vaccari, M; Driver, S; Taylor, E; Franzen, T; Brown, M J I; Shabala, S; Andernach, H; et al.
ABSTRACT: We present the Australian Square Kilometre Array Pathfinder (ASKAP) observations of the Galaxy and Mass Assembly (GAMA)-23h field. The survey was carried out at 887.5 MHz and covers an ∼83 square deg field. We imaged the calibrated visibility data, taken as part of the Evolutionary Mapping of Universe Early Science Programme, using the latest version of the ASKAPSoft pipeline. The final mosaic has an angular resolution of 10 arcsec and a central rms noise of around 38 $μ$ Jy beam −1 . The derived radio source catalogue has 39 812 entries above a peak flux density threshold of 5σ. We searched for the radio source host galaxy counterparts using the GAMA spectroscopic (with an i -band magnitude limit of 19.2 mag) and multiwavelength catalogues that are available as part of the collaboration. We identified hosts with GAMA spectroscopic redshifts for 5934 radio sources. We describe the data reduction, imaging, and source identification process, and present the source counts. Thanks to the wide area covered by our survey, we obtain very robust counts down to 0.2 mJy. ASKAP's exceptional survey speed, providing efficient, sensitive, and high-resolution mapping of large regions of the sky in conjunction with the multiwavelength data available for the GAMA23 field, allowed us to discover 63 giant radio galaxies. The data presented here demonstrate the excellent capabilities of ASKAP in the pre-SKA era.